2020
DOI: 10.4491/eer.2020.454
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of zinc oxide and silver nanoparticles using ficus palmata - Forssk leaf extracts and assessment of antibacterial activity

Abstract: Multidrug resistance of bacteria is an emerging human health hazard and warrants development of novel antibacterial agents with more effective mode of action. Here, zinc oxide and silver nanomaterials were prepared using Ficus palmata Forssk leaf extract with efficient antibacterial activity. SEM coupled with EDS confirmed the spherical symmetry with average particle diameter 50 to 65 nm while the XRD confirmed crystalline face centered cubic structure of silver and hexagonal crystallize phase of zinc oxide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) of ZnONPs for Staphylococcus aureus and Escherichia coli were reported as 12.5 and 6.25 µg/ml, respectively [64]. Wherase, Shamshad et al [65] found that MIC of ZnONPs was 100, 11.1 and 3.7 μg/ml for Staphylococcus aureus, Pseudomonas aeruginosa and E coli, respectively.…”
Section: Antimicrobial Activity Of Znonpsmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of ZnONPs for Staphylococcus aureus and Escherichia coli were reported as 12.5 and 6.25 µg/ml, respectively [64]. Wherase, Shamshad et al [65] found that MIC of ZnONPs was 100, 11.1 and 3.7 μg/ml for Staphylococcus aureus, Pseudomonas aeruginosa and E coli, respectively.…”
Section: Antimicrobial Activity Of Znonpsmentioning
confidence: 99%